If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(-x-6)=-9(-3x-10)
We move all terms to the left:
-3(-x-6)-(-9(-3x-10))=0
We add all the numbers together, and all the variables
-3(-1x-6)-(-9(-3x-10))=0
We multiply parentheses
3x-(-9(-3x-10))+18=0
We calculate terms in parentheses: -(-9(-3x-10)), so:We get rid of parentheses
-9(-3x-10)
We multiply parentheses
27x+90
Back to the equation:
-(27x+90)
3x-27x-90+18=0
We add all the numbers together, and all the variables
-24x-72=0
We move all terms containing x to the left, all other terms to the right
-24x=72
x=72/-24
x=-3
| 5(-3x-1)=25 | | -3(-x-6)=-9(-3x-10 | | 3x–25+16=12 | | 3y/4=y/2+6 | | -14=2x-4(-x-10) | | 9.5x=167.2 | | 5y=18-4y | | 34=w- | | 2.6x-5.7=-0.5 | | –5−3q=–2q | | 20=10-1x | | 52=-38+6y | | 7h+5=5+7h | | -4x-6(-4x-10)=-60 | | 11w=8250w= | | 5+8(6x+9)=5-6(8x+3) | | 2x+6(7x+19)=-150 | | 33h=33 | | 18^p+6+5=39 | | 20+20+9h=–20+6h | | 6y/8-6=y | | h-9=16 | | 7n-14=31 | | 2(1-7a)=38 | | -7(4x+2)=10x+5 | | -140=-20n | | 5x+3x-4=90 | | d/2=11 | | f/28=18 | | –15=3(6+v) | | -9v=945 | | r-11=33 |